2023
DOI: 10.1021/acschembio.3c00328
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Substrate Recognition by the Unusual Nitrating Enzyme RufO

Abstract: Nitration reactions are crucial for many industrial syntheses; however, current protocols lack site specificity and employ hazardous chemicals. The noncanonical cytochrome P450 enzymes RufO and TxtE catalyze the only known direct aromatic nitration reactions in nature, making them attractive model systems for the development of analogous biocatalytic and/or biomimetic reactions that proceed under mild conditions. While the associated mechanism has been well-characterized in TxtE, much less is known about RufO.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, a cytochrome P450 enzyme (TxtE) was shown to catalyze tryptophan nitration using NO and O 2 [ 10 ]. Similar aromatic nitration mediated by a NOS/P450 pair (RufN/RufO or IlaM/IlaN) was also found in the biosynthesis of rufomycins/ilamycins [ [11] , [12] , [13] , [14] ]. In addition, we recently showed that the N8 atom in the unique 1,2,3-triazole heterocycle of the antiviral agent 8-azaguanine derives from NO, which is synthesized by a NOS (PtnF) [ 15 ].…”
Section: Introductionmentioning
confidence: 76%
“…Subsequently, a cytochrome P450 enzyme (TxtE) was shown to catalyze tryptophan nitration using NO and O 2 [ 10 ]. Similar aromatic nitration mediated by a NOS/P450 pair (RufN/RufO or IlaM/IlaN) was also found in the biosynthesis of rufomycins/ilamycins [ [11] , [12] , [13] , [14] ]. In addition, we recently showed that the N8 atom in the unique 1,2,3-triazole heterocycle of the antiviral agent 8-azaguanine derives from NO, which is synthesized by a NOS (PtnF) [ 15 ].…”
Section: Introductionmentioning
confidence: 76%
“…Our investigations into the function of RufO stemmed from comparisons between its structure (23,24) and that of the biarylitide crosslinking P450Blt that we had recently characterized (26). Analysis of these structures revealed that they were highly similar (41.6% amino acid ID, C-a RMSD 1.8 Å to 8SPC; Figure S6), apart from mutations at a key section of the RufO I-helix involved in oxygen activation (27).…”
Section: Cytochrome P450 Rufo Nitrates a Ripp Precursor Peptidementioning
confidence: 99%
“…Due to the similarity of the genes rufNO to the txtDE system, which has been demonstrated to perform nitration of tryptophan in thaxtomin biosynthesis (13), the rufomycin 3-NO2-Tyr residue has been postulated as being synthesized by an analogous mechanism involving direct nitration of free Tyr (15). However, this hypothesis is not supported by reported data, and recent studies suggest RufO instead acts on Tyr bound to a carrier protein domain following selection and activation by the NRPS machinery (22)(23)(24).…”
mentioning
confidence: 99%